PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING DALAM MENGEVALUASI KINERJA KARYAWAN UNTUK MEMILIH KARYAWAN TELADAN DI PT. SRITEX, TBK(DEPT. SPINNING V) SUKOHARJO - Wawan Laksito YS, Rina Endarti, Andriani Kusumaningrum (Jurnal Ilmiah SINUS, 2015)
Spinning Department V is one of the Spinning Department at PT. Sritex, Tbk. In spur the spirit of employees to improve of dedication andÂ  their performance, thenÂ  awarded award by selecting the model employee who conducted periodically. The purpose of this study was to create a system of computerized Decision Evaluating Employee Performance Model select employees using Simple Additive Weighting (SAW). To use this application, the administrator must first be included in the process. In terms of design applications, these applications using HTML and PHP software. Discover additive weighting method is a simple method that is able to provide support in the decision making process for each prospective employee of the month as a result of the selection by the system have the same accuracy to determine the quality of the selection of employees is done manually by the system that existed before Keywords: Employee, Performance Criteria, Simple Additive weighting